Natural regeneration in edge and interior of a forest fragment at the Catarinense Plateau - Oliveira Cabral Hassan, Victória; Lamounier da Silva Lima, Bianca; Martins Artismo, Marciano; Higuchi, Pedro; Pereira Gomes, Juliano (Floresta, 2024)
Forest fragmentation is one of the greatest challenges for forest conservation in the Catarinense Plateau region. Thus, this work aimed to evaluate the edge effect on the structure and floristics of natural tree regeneration in a fragment of Mixed Ombrophylous Forest in São José do Cerrito, Santa Catarina. The natural regeneration of the tree component in the understory was sampled in four transects placed perpendicular to the edge of the fragment. Eight plots of 20 m² were installed on the edge (contact with the surrounding matrix) and inside (100 m from the edge) of the fragment, subdivided into smaller plots according to the class of regenerants. The regenerants were identified, measured in height and classified according to their successional group, conservation status, endemism and calculated the regeneration index for each class of height and total. For statistical analysis, Non-Metric Multidimensional Scaling (NMDS) analysis was used. The results showed a significant difference between the interior and edge of the fragment, with the regenerating community on the edge being significantly more abundant and more diverse than the interior. The species with the highest rate of total regeneration towards the interior were Myrcia hatschbachii (TNR=12.1%) and Banara tomentosa (TNR=11.1%), and towards the edge it was Myrcia oblongata (TNR=15.1%). It is concluded that the edge effect appears to have been a determining factor for the alteration in the structure and floristic composition of the regenerants.